Green supply chain management for sustainable business practice - Khan, Mehmood, 1973-; Hussain, Matloub, 1973-; Ajmal, Mian M. (Business Science Reference, 2017)
"This book examines the challenges and benefits of implementing sustainability into the core functions of contemporary enterprises, focusing on how green approaches improve operations in an ecological way by highlighting key concepts, emerging innovations, and future directions"- Resumé vydavatele